(untitled) (Revista Archai, 2025)
The article analyzes the parallels between the supposed fragments of the Oracles of Hystaspes in the seventh book of Lactantius’ Divine Institutes and the Apocalypse of John, specifically in chapters 11:3-12, on the "two witnesses" and 13:11-16, on the action of the Beast. The article presents the scholarship on the issue and the possibilities of appropriation of Zoroastrian themes by John of Patmos in his apocalypse, especially in the combat myth.